Nanoparticle-Encapsulated Bryostatin-1 Activates α-Secretase and PKC Isoforms In vitro and Facilitates Acquisition and Retention of Spatial Learning in an Alzheimer's Disease Mouse Model - Schrott, Lisa; Yi, Ping; Jackson, Kasey; Jackson, Gabriel S.; Webb, Christopher; Minagar, Alireza; Yun, J. W.; Purdum, Geoffrey; Rios, David J.; Tyler, Theodore A.; Vizcanio, Maria I.; Castor, Judith L.; et al. (Current Alzheimer Research, 2020)
Background: Alzheimer’s disease (AD) animal models have revealed neuroprotective actions of Bryostatin-1 mediated by activation of novel PKC isoforms, suppression of beta-amyloid and downregulation of inflammatory and angiogenic events, making Bryostatin-1 an attractive candidate for attenuating AD-associated neural, vascular, and cognitive disturbances. Objective: To further enhance Bryostatin-1 efficacy, nanoparticle-encapsulated Bryostatin-1 formulations were prepared. Methods: We compared nano-encapsulated and unmodified Bryostatin-1 in in vitro models of neuronal PKC-d, PKC-e isoforms, α-secretase and studied nano-encapsulated Bryostatin-1 in an AD mouse model of spatial memory (BC3-Tg (APPswe, PSEN1 dE9) 85Dbo/J mice). Results: We found that nanoencapsulated Bryostatin-1 formulations displayed activity greater or equal to that of unmodified Bryostatin-1 in PKC-δ and -ε and α-secretase activation assays. We next evaluated how treatment with a nanoencapsulated Bryostatin-1 formulation facilitated spatial learning in the Morris water maze. AD transgenic mice (6.5 to 8 months of age) were treated with nanoparticle encapsulated Bryostatin-1 formulation (1, 2.5, or 5 μg/mouse) three times the week before testing and then daily for each of the 5 days of testing. Across the acquisition phase, mice treated with nanoencapsulated Bryostatin-1 had shorter latencies, increased % time in the target zone and decreased % time in the opposite quadrant. The mice were given retention testing after a 2-week period without drug treatment. Mice treated with nanoencapsulated Bryostatin-1 had shorter latencies to find the escape platform, indicating retention of spatial memory. Conclusion: These data suggest that cognitive deficits associated with AD could be treated using highly potent nanoparticle-encapsulated formulations of Bryostatin-1.
Keywords: PKC